Multi-physics simulation of in-flight ice shedding. Issue 1 (January 2021) - Rausa, A.; Guardone, A.
Abstract: In-flight ice accretion may possibly jeopardise the safety of fixed-and rotary-wing aircraft. Icing can possibly occur if supercooled water droplets in clouds impinge on the aircraft surfaces and freeze upon impact. A major issue related to ice accretion is the possibility of ice shedding from the main body and impacting other parts of the aircraft or being ingested by the engines. A multi-physics framework is presented to simulate ice accretion and shedding from wings and engine nacelles due to aerodynamic forces. The aerodynamics is computed using the open-source tool-kit SU2. Cloud droplet trajectories are computed using the arbitrary-precision Lagrangian in-house solver PoliDrop. Then, the in-house ice accretion tool-kit PoliMIce is used to determine the ice layer. A FEM structural analysis is performed on the accreted ice shape by means of the open-source code MoFEM. Internal stresses within the ice geometry due to aerodynamic forces are computed. The possibility of the occurrence of cracks in the ice layer is assessed and its propagation is determined numerically. Two-dimensional ice accretion simulations are performed to check the validity of the present approach and compare fairly well with available results.